A Model for the Selection of Active Learning While Taking into Account Modern Student Behavior Styles - Inessa Sytnik; Artem Stopochkin (MDPI AG, 2023)
This paper solves the complex scientific and practical problem of developing the critical thinking skills of the modern student. The solution of the indicated problem was accomplished by generalizing contemporary scientific works and conducting an empirical study (survey) of university students. The conducted research made it possible to distinguish students' behavior styles according to seven criteria: the student's level of trust in the higher education system; the student's tendency to cheat the education system; the student's degree of self-reliance and self-confidence; the student's degree of disappointment with the education system; the student's degree of involvement in the education process; the student's degree of social inclusion; and the student's degree of dependence on formal learning results. In this research, we determined the effectiveness of different teaching methods and proved that the student's preference of teaching methods depends on their behavior styles. This means that in order to increase the effectiveness of the educational process, the academic teacher must select teaching methods while taking into account the behavior styles of the students. To this end, the article develops a model for the selection of active learning methods, taking into account the behavior styles of modern students, and conducts an approval of this model.